Laboratory and Field Effectiveness of Selected Insecticides m Preventing Adult Emergence of Dacus dorsalis Hendel (Diptera: Tephritidae) - Mohamad, Rosli; Ibrahim, Yusof; Saud, Samsudin (1979)
Four insecticides were tested in the laboratory and field on their relative efficacy against the larvae and pupae of Dacus dorsalis Heudel. In the laboratory studies all the insecticides 'were found to he effective against the larvae although they were comparatively less effecive against the pupae in preventing adult emergence. In general, field insecticidal treatments resulted in lower numbers of adult emergence as compared to the laboratory treatments.